2019
DOI: 10.1016/j.neurobiolaging.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Impaired perceptual integration and memory for unitized representations are associated with perirhinal cortex atrophy in Alzheimer's disease

Abstract: Unitization, the capacity to encode associations as one integrated entity, can enhance associative memory in populations with an associative memory deficit by promoting familiarity-based associative recognition. Patients with Alzheimer's Disease (AD) are typically impaired in associative memory compared with healthy controls, but do not benefit from unitization strategies. Using fragmented pictures of objects, this study aimed at assessing which of the cognitive processes that compose unitization is actually a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 102 publications
2
14
0
Order By: Relevance
“…Knowledge about unique entities like faces has been shown to be impaired early in AD due to tau pathology in subhippocampal structures (entorhinal and perirhinal cortices) (Braak and Braak, 1995), thus disrupting semantic retrieval (Didic et al, 2011). This interpretation is also consistent with the finding that the advantage of unitization for alleviating the associative memory deficit is absent in early AD patients (D'Angelo et al, 2016), in relation to perirhinal cortex atrophy (Delhaye et al, 2018(Delhaye et al, , 2019.…”
Section: The Perirhinal Cortex Is Involved In Successful Pre-experimesupporting
confidence: 90%
“…Knowledge about unique entities like faces has been shown to be impaired early in AD due to tau pathology in subhippocampal structures (entorhinal and perirhinal cortices) (Braak and Braak, 1995), thus disrupting semantic retrieval (Didic et al, 2011). This interpretation is also consistent with the finding that the advantage of unitization for alleviating the associative memory deficit is absent in early AD patients (D'Angelo et al, 2016), in relation to perirhinal cortex atrophy (Delhaye et al, 2018(Delhaye et al, , 2019.…”
Section: The Perirhinal Cortex Is Involved In Successful Pre-experimesupporting
confidence: 90%
“…SOM interneurons are low-threshold spiking cells that generally target the more distal dendrites of pyramidal cells, which receive excitatory input (31,65,81) thus likely regulating the dendritic integration of the excitatory synaptic inputs (16). Recently, SOM neurons have been identified as regulators of beta/low gamma (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) oscillations in the neocortex (83), thus a loss of these interneurons could reduce the activity in this frequency range affecting overlying processes. In this sense, the participation of SOM cells in synaptic plasticity and memory processes has been widely documented (49,87), and it has been suggested that a downregulation of somatostatin, and in consequence the levels of the Abeta-cleaving enzyme neprilysin, is a main risk factor for the development of AD (30).…”
Section: Discussionmentioning
confidence: 99%
“…This is a subregion of the parahippocampal gyrus composed of two subdivisions, Brodmann areas 35 and 36, also known as transentorhinal cortex and ectorhinal cortex, respectively, and represents an important component of the medial temporal memory system, linking sensory association cortices with the hippocampal formation . This cortical region plays an essential role in higher cognitive functions including episodic memory (recollection), semantic memory (familiarity) and visual perceptual processing systems , indeed, lesions of the perirhinal cortex lead to recognition memory impairment . Despite its relevance in memory processes, and the fact that the area 35 of the perirhinal cortex is the first cortical region to be affected by neurofibrillary pathology in AD patients (Braak I stage) the perirhinal cortex has been, however, surprisingly understudied at the neuropathological level in AD patients or animal models, and no studies have been performed so far to determine the AD‐associated GABAergic neuronal vulnerability in this cortical region.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in this study, as in most previous studies, the source of this impairment remains uncertain, whether it is in the creation of a unitized and integrated representation at the encoding stage or in the subsequent recognition stage. Only one study previously suggested that both the capacity to form a complex and integrated representation at an initial processing stage and the recognition of unitized associations were impaired in AD, but this was for perceptual unitization (Delhaye et al, 2019). Here, one possible explanation could be that some conceptual impairments, or subtle difficulties with semantic memory in MCI patients (Joubert et al, 2008), as suggested by their impaired conceptual fluency scores in this study, could have led patients to some difficulty properly combining the concepts in the high-unitization condition.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in AD, the few existing studies on this topic have failed to find any benefit from unitization to mitigate patients' associative memory deficit (Bastin et al, 2014). It is possible that the substantial NFT pathology in PrC prevents AD patients from efficiently recruiting the PrC to effectively perform unitization by hampering the formation of a complex integrated representation (Delhaye, Bahri, Salmon, & Bastin, 2019).…”
mentioning
confidence: 99%